Influence of Price and Promotion on the Purchasing Decision of Event Organizer Services PT Showbitz Mitra Utama Medan - Theresia Uli Ritonga; Enda Yunita Surbakti (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
Every company has a goal to win the competition and maximize company profits by attracting consumers from the suitability of set prices and effective and efficient promotions. Both of these are factors that can convince consumers to make a purchase decision. This research aims to determine the effect of price and promotion on the purchase decision for event organizer services. This research is a quantitative descriptive research with data sources used, namely literature studies and distributing questionnaires. The sample in this research was 35 respondents with saturated sampling techniques. The data analysis method in this research used data quality test, classical assumption test, multiple linear regression analysis and hypothesis test using SPSS version 20 program. The results of t test in this research to show that the price (X1) partially has a positive and significant influence on the purchase decision for event organizer services with a calculated t value of 3,186. The results of t test in this research to show that the promotion (X2) partially has a positive and significant influence on the purchase decision for event organizer services with a calculated t value of 5,812. The results of the F test on price (X1) and promotion (X2) simultaneous has a positive and significant influence on the purchase decision for event organizer services with a calculated F count of 21,152. The results of the Adjusted R Square (R2) test to show that price (X1) and promotion (X2) are able to influence the purchase decision for event organizer services by 54,2% and the remaining 45,8% can be explained by factors not axamined in this research.